Is trigonitis a neglected, imprecise, misunderstood, or forgotten diagnosis?. Issue 4 (15th April 2019) - Sadeghi, Zhina; MacLennan, Gregory; Childs, Stacy J.; Zimmern, Philippe E.
Abstract: To consolidate our understanding of "trigonitis" and its relevance in current urologic practice, we reviewed the literature on this entity. The MEDLINE, EMBASE, and Cochrane databases (1905 to present) were systematically reviewed for any English language articles addressing the following terms: trigonitis, cystitis trigoni, cystitis cystica, squamous metaplasia, pseudomembranous trigonitis, vaginal metaplasia, infection or inflammation of the trigone, and trigonitis in recurrent urinary tract infections (rUTI). Abstracts or articles not focused on trigonitis, or those only repeating findings from other original articles on trigonitis, and studies in children or men were excluded. Reported histologic findings on trigonitis, theories regarding its pathophysiology, and therapeutic strategies were reviewed. From 57 relevant articles, only 27 focused on trigonitis. Cystoscopic evaluation of the trigone described inflammatory lesions of cystitis cystica, occasionally small stones or pus‐filled lesions, an appearance that should be differentiated from white patches of squamous metaplasia. Embryologic formation of the trigone, history of rUTIs, and effects of hormones on the trigone have been proposed as underlying pathophysiologic mechanisms. Numerous therapeutic strategies have been reported to treat symptomatic trigonitis, including antibiotic therapy, intravesical instillation of different agents, electrofulguration, and laser coagulation. However, no treatment indication criteria have been well established so far, and long‐term data are lacking. Despite several reports describing histologic and endoscopic findings of trigonitis, its prevalence, pathophysiology, and treatment have remained poorly defined. Its relevance in the management of rUTIs should be further evaluated.